The Activities of Naqshbandiyya Among Kyrgyz - KADYROV, Mederbek (Scientific Journal of Faculty of Theology, 2017)
Sufi orders played an important role in spreading Islam among Kyrgyz people. One of the most active order among the Kyrgyz was Naqshbandiyya.The activities of Naqshbandi order began to spread among the Kyrgyz to the and of the XIV century and continued with the jamaats Ishaqiyya and Afaqiyya. Kyrgyz tribes also took place in the political rivalry between the two jamaats. Naqshbandiyya left a deep imprint on Kyrgyz culture.